Between Reformation and Over-fitting: A Critical Evaluation of Holger M. Zellentin’s Qurʾanic Intertextuality - Muhammad Farhan Rahardian; Muhammad Faidhur Rabbani; Nadya Putri Prameswari (Al-Bayan: Jurnal Studi Al-Qur'an dan Tafsir, 2026)
Western Qur'anic scholarship has progressively abandoned Orientalist paradigms of textual plagiarism, relocating the scripture within the dynamic epistemic space of Late Antiquity. This study critically systematizes Holger M. Zellentin’s trialogical framework, evaluating the methodological tension between robust historical contextualization and the acute risk of textual over-fitting. Utilizing an elaborative-critical qualitative methodology, this research conducts a hermeneutic reading and cross-cultural thematic triangulation of Zellentin’s foundational corpus, specifically analyzing his longitudinal tracing of late antique legal codes and prophetic narratives. The analysis demonstrates that Zellentin successfully elevates the Qurʾan to the status of an active reformer that critically integrates and supersedes Judeo-Christian traditions. By mapping Qur'anic penal injunctions and incest prohibitions against Justinian decrees and Syriac marriage laws, and juxtaposing the miracles of Jesus against the polemical Toledot Yeshu, Zellentin provides granular evidence of a sophisticated textual trialogue. Nevertheless, this relentless genealogical tracking forces a strict dependency on external biblical and Byzantine antecedents. Such microscopic intertextuality inadvertently flattens the scripture’s internal prophetological architecture, reducing its sovereign theological pronouncements to reactive editorial synthesis and neglecting its intrinsic structural unity. Ultimately, this research advocates for a methodological equilibrium that incorporates the pluricultural debates of the Late Antique milieu without subordinating the Qurʾan’s independent theological rationale and absolute distinctive nature (Eigengesetzlichkeit) to its historical precursors.